Living-donor liver transplantation: 12 years of experience in Asia - Chao‐Long Chen; Irene Oi‐Lin Ng; Sung‐Gyu Lee; Masatoshi Makuuchi; Kōichi Tanaka (2003)
Living-donor liver transplantation has provided a solution to the severe lack of cadaveric grafts for the replacement of livers afflicted with end-stage cirrhosis, fulminant disease, or inborn errors of metabolism. The pioneering experience in Japan in the early 1990s helped open wide the avenues of a new branch of science that is technically demanding and whose benefits are clearly dramatic. The need for alternative sources of liver grafts was common to the entire Asian region and, fortunately, the option of obtaining partial liver grafts from live donors had already become tenable. By the second half of the past decade, living-donor liver transplant programs had been successfully established in Hong Kong, Taiwan, and Korea. More than 1,500 cases have been performed over a 12-year period. This report describes the cumulative experience in living-donor liver transplantation in Asia on the basis of data from five major liver transplant centers.